Design and development of wideband antennas for V2X communications - Mei, Dongni (2017)
This final year project aims to innovatively design wideband antennas with optimal pattern for efficient V2X system by using HFSS simulation software. Totally 5 printed planar antennas in 2 different types, 2 of which are compact coplanar Vivaldi antenna and 3 of which are rectangular aperture antenna, are designed by the author for wideband vehicle antenna. All the antennas are designed to have a wide bandwidth, an optimal radiation pattern and a compact dimension. The coplanar Vivaldi antennas are designed to have a bandwidth from 0.75GHz to 2.75GHz. FR4 and TLY5 are used for the substrate material of the antenna. In order to further minimize the antenna dimension, and enhance the omnidirectional radiation pattern of Vivaldi antenna at the horizontal plane, TLY5 curved antenna is designed and fabricated in the project. The comparison between flat and curved antenna will be discussed in this final year project report. The rectangular aperture antennas are designed to have a bandwidth from 2.4 GHz to 6GHz. Three aperture antennas with different exciting stub pattern are designed, fabricated and analysis in this final year report. This final year report summaries all the procedures and results of these 5 designed antennas. The Introduction, Literature Review, Design & Analysis, Simulation & Analysis, Hardware Fabrication & Measurement Setup, Result Discussion & Analysis, and Conclusion & Future work will be included and elaborated in this final year project report.